It takes two to Tango: Lobbies and the political business cycle - Daniel Horgos; Klaus W. Zimmermann (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2009)
With interest groups significantly affecting economic performance (according to Mancur Olson) and a vital interest of governments in economic growth and low unemployment in order to win elections, there should be a link between political business cycles and the evolution of lobbies over time which has totally been ignored in the literature up to now. In modeling this link in a theoretical and empirical way we try to answer two questions: Is it possible to interpret Olson's Law of Interest Groups not only as a long run phenomenon but also in a short-run perspective, integrating it into the theory of political business cycles? And: is there any empirical evidence that a typical pattern of lobby behavior and macroeconomic status exists which is consistent over a couple of election periods? In order to investigate these issues, we first analyze some literature that is usually ignored in the more technical contributions evaluating Olsons law, but proves to be highly important as background for answering the above mentioned questions. We then illustrate how a model consisting of Olsons interest-groups theory and the endeavors of governments to win the majority of votes in elections could look like, before we perform a time-series-analysis based on the lobby-list of the German Bundestag in order to gain some more insights into the relationships between lobbies, governments and voters. As a result we discover a consistent behavior of the lobbies over the cycle that boils down to some kind of non-aggression pact between the lobbies and the governments irrespective of their political alignments.
urn:nbn:de:gbv:705-opus-20930
Keywords: D72; D78; 330; interest groups; political business cycles; growth; unemployment; inflation; Interessenvertretung; Interessenpolitik; Wirkungsanalyse; Politischer Konjunkturzyklus; Wirtschaftswachstum; Arbeitslosigkeit; Inflation; Deutschland